Optimisasi Pemuatan Barang Untuk Memaksimalkan Utilitas Volume Kontainer Menggunakan Software CubeMaster Pada Perusahaan Distribusi Bubuk Fragrance - Sintia Basliana; Winarno Winarno (Jurnal Ilmiah Wahana Pendidikan, 2022)
Companies must be able to improve product quality, reduce production costs and manage products optimally in order to compete and survive in the manufacturing world. One of the efforts to make it happen is by arranging goods into warehouses, managing containers and transportation by paying attention to the exhibition of warehouse activities. The arrangement of goods into containers is one of the important factors in the distribution sector to be able to act effectively and efficiently. Preparation of goods that is done manually can take a long time and increase the distribution costs incurred. The problem that exists is in the process of goods activities that are not optimal. This is observed from the existence of finished goods that cannot be loaded into container trucks at one time loading and unloading goods. For this reason, this study aims to maximize the utility of the container. After data processing using CubeMaster software produces a container fitness value of 87.98% which previously used container capacity in real conditions of 87.70%, there is an increase in capacity use in containers which are expected to provide input in the process of preparing goods into containers